Comprehensive guide to 5G security - Liyanage, Madhusanka; Ahmad, Ijaz, 1985-; Abro, Ahmed Bux; Gurtov, Andrei; Ylianttila, Mika (Hoboken, NJ : John Wiley & Sons, 2018)
The first comprehensive guide to the design and implementation of security in 5G wireless networks and devices Security models for 3G and 4G networks based on Universal SIM cards worked very well. But they are not fully applicable to the unique security requirements of 5G networks. 5G will face additional challenges due to increased user privacy concerns, new trust and service models and requirements to support IoT and mission-critical applications. While multiple books already exist on 5G, this is the first to focus exclusively on security for the emerging 5G ecosystem. 5G networks are not only expected to be faster, but provide a backbone for many new services, such as IoT and the Industrial Internet. Those services will provide connectivity for everything from autonomous cars and UAVs to remote health monitoring through body-attached sensors, smart logistics through item tracking to remote diagnostics and preventive maintenance of equipment. Most services will be integrated with Cloud computing and novel concepts, such as mobile edge computing, which will require smooth and transparent communications between user devices, data centers and operator networks. Featuring contributions from an international team of experts at the forefront of 5G system design and security, this book: -Provides priceless insights into the current and future threats to mobile networks and mechanisms to protect it -Covers critical lifecycle functions and stages of 5G security and how to build an effective security architecture for 5G based mobile networks -Addresses mobile network security based on network-centricity, device-centricity, information-centricity and people-centricity views -Explores security considerations for all relative stakeholders of mobile networks, including mobile network operators, mobile network virtual operators, mobile users, wireless users, Internet-of things, and cybersecurity experts Providing a comprehensive guide to state-of-the-art in 5G security theory and practice, A Comprehensive Guide to 5G Security is an important working resource for researchers, engineers and business professionals working on 5G development and deployment.
4.4.2 Control Channels Security 89 4.4.3 Traffic Monitoring 91 4.4.4 Access Control 91 4.4.5 Network Resilience 91 4.4.6 Security Systems and Firewalls 92 4.4.7 Network Security Automation 92 4.5 Conclusions and Future Directions 94 4.6 Acknowledgement 95 References 95 5 Cyber Security Business Models in 5G 99; Julius Francis Gomes, Marika Iivari, Petri Ahokangas, Lauri Isotalo, Bengt Sahlin
Print version record and CIP data provided by publisher.
Includes bibliographical references and index.
Keywords: Mobile communication systems -- Security measures; Wireless communication systems -- Security measures; COMPUTERS -- Programming -- Mobile Devices; COMPUTERS -- Security -- General; Wireless communication systems -- Security measures; Electronic books